The echocardiography of replacement heart valves - John B Chambers (Echo Research and Practice, 2016)
This is a practical description of how replacement valves are assessed using echocardiography. Normal transthoracic appearances including normal variants are described. The problem of differentiating normal function, patient–prosthesis mismatch and pathological obstruction in aortic replacement valves with high gradients is discussed. Obstruction and abnormal regurgitation is described for valves in the aortic, mitral and right-sided positions and when to use echocardiography in suspected infective endocarditis. The roles of transoesophageal and stress echocardiography are described and finally when other imaging techniques may be useful.